Differential effects of strength determinants on different phases of olympic rowing performance in adolescent athletes - Romina Jessica Ledergerber; Mats Willem Jacobs; Ralf Roth; Moritz Schumann (Bern Open Publishing, 2023)
Background Olympic rowing relies heavily on aerobic metabolism, but the demands on strength and power have not yet been thoroughly investigated (Lawton et al., 2011). As the characteristic pacing strategy compounds an initial start sprint, a sustained middle section and end spurt, the neuromuscular and physiological requirements of the particular phases need to be considered more closely (Garland, 2005; Mikulic, 2011). Therefore, the purpose of this study was to identify strength qualities for distinct phases in rowing performance in adolescent athletes. Methods The cross-sectional analysis of fourteen national competitive rowing athletes (4 female; 10 male) included anthropometrics, isometric and isokinetic leg press, back extension and flexion, isometric mid-thigh pull (MTP) and handgrip strength, VO2max, and a 2000 m time trial, in which peak forces were measured in the start, middle and end phase. The rate of force developments (RFD) were obtained for isometric leg press (150 and 350 ms) and MTP (150 ms and 300 ms). Stepwise regression models were created for ergometer performance in the start, middle and end phases. Results The best fit model for the start phase included isometric back extension and RFD 300 ms of MTP (R2 = 0.912, p < 0.001), while for the middle section it were VO2max, isometric leg press and sitting height (R2 = 0.844, p < 0.001). For the end phase a best fit was observed for isometric back flexion, RFD 350 ms of leg press, body height and sex (R2 = 0.965 p < 0.001), whereas absolute VO2max, isokinetic back flexion and sex explained variance over the entire 2000 m time trial (R2 = 0.975, p < 0.001). Conclusion For the high acceleration at the start, force transmission through maximum back strength seems to be essential, while fast power production along the kinetic chain is also relevant (Baudouin & Hawkins, 2002). In addition to VO2max, produced maximum strength in the leg press explains the importance for the force production of the sustained middle section (Cosgrove et al., 1999). These results indicate that maximal force complements the reliance on VO2max, as well as neuromuscular parameters and maximal force transmission seems to be important for the start phase. Further research through intervention studies is needed to refine training recommendations. References Baudouin, A., & Hawkins, D. (2002). A biomechanical review of factors affecting rowing performance. British Journal of Sports Medicine, 36(6), 396-402. http://dx.doi.org/10.1136/bjsm.36.6.396 Cosgrove, M. J., Wilson, J., Watt, D., Grant, S. F. (1999). The relationship between selected physiological variables of rowers and rowing performance as determined by a 2000 m ergometer test. Journal of Sports Sciences, 17(11), 845-852. https://doi.org/10.1080/026404199365407 Garland, S. (2005). An analysis of the pacing strategy adopted by elite competitors in 2000 m rowing. British Journal of Sports Medicine, 39(1), 39-42. https://doi.org/10.1136/bjsm.2003.010801 Lawton, T. W., Cronin, J. B., & McGuigan, M. R. (2011). Strength testing and training of rowers: A review. Sports Medicine, 41(5), 413-432. https://doi.org/10.2165/11588540-000000000-00000 Mikulic, P. (2011). Maturation to elite status: A six-year physiological case study of a world champion rowing crew. European Journal of Applied Physiology, 111(9), 2363-2368. https://doi.org/10.1007/s00421-011-1870-y